STRATEGI PEMASARAN DIGITALISASI PRODUK USAHA MIKRO, KECIL DAN MENENGAH (UMKM) KEMPLANG DI KELURAHAN MARIANA ILIR - Anggun Apriani; Indah Pusnita; Mia Anggraini (Bajang Institute, 2023)
Micro, Small and Medium Enterprises (MSME) have proven to contribute to the Indonesian economy, including of course the Kemplang MSME in Mariana Ilir Village. Through marketing socialization on product digitization as a form of community service, we conducted direct interviews with Kemplang MSMEs and several residents and representatives of the Mariana Ilir Village government. I got a lot of information regarding the problems of MSME actors and the obstacles in product marketing, all of which aim to improve the social welfare and socio-economic conditions of business actors. The strategy adopted by MSME players is to develop partnerships with large companies; establishing and enhancing cooperative relations with suppliers, modern retail and the government; increase the competitiveness of both branding and packaging; utilizing information technology as a means of promotion and expanding digital market networks; maintain and improve the quality of products that are healthier in the context of price competition; improve the quality of human resources in terms of management and marketing; and manage the supply chain of raw materials and finished products effectively and efficiently. Everything has started to be done by these business actors after receiving socialization, but not so optimal. Then there are also several other obstacles faced by business actors in carrying out product marketing, namely the lack of product development, marketing with social media, and simple bookkeeping